2022
DOI: 10.3389/fnut.2022.931171
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Intake From Cocoa-Based Products and Adiposity Parameters in Adolescents in Spain

Abstract: BackgroundCocoa-based products are a good source of flavonoids, which may have beneficial effects on metabolic health.ObjectiveThe aim of this study is to assess the relationship between flavonoids from cocoa-based products and adiposity parameters in adolescents.MethodsA cross-sectional study was conducted involving 944 adolescents aged 11–14 years enrolled in the SI! Program for Secondary Schools trial in Spain with available baseline data from food frequency questionnaires and anthropometric measurements [w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In our sample population, flavonoids were the most consumed phenolic compounds, the highest energy-adjusted intake being associated with a lower WC z-score and HDL-c compared to the lowest intake. In a previous study, we found that flavonoids from cocoa-based products (among the major food contributors to flavonoid intake) were associated with lower adiposity parameters, such as the WC z-score and waist-height ratio, and a lower probability of having abdominal obesity [13]. Results from the TOSCA.IT cohort indicated that T2DM adults with a high flavonoid intake had lower levels of TG, SBP, and DBP [39].…”
Section: Dietary Intake Of (Poly)phenol Subclasses and Cardiometaboli...mentioning
confidence: 90%
See 1 more Smart Citation
“…In our sample population, flavonoids were the most consumed phenolic compounds, the highest energy-adjusted intake being associated with a lower WC z-score and HDL-c compared to the lowest intake. In a previous study, we found that flavonoids from cocoa-based products (among the major food contributors to flavonoid intake) were associated with lower adiposity parameters, such as the WC z-score and waist-height ratio, and a lower probability of having abdominal obesity [13]. Results from the TOSCA.IT cohort indicated that T2DM adults with a high flavonoid intake had lower levels of TG, SBP, and DBP [39].…”
Section: Dietary Intake Of (Poly)phenol Subclasses and Cardiometaboli...mentioning
confidence: 90%
“…Moreover, a panel of experts on (poly)phenols has developed the first-ever guideline recommendations for dietary flavanol or flavan-3-ol intake, highlighting the role of this subclass of flavonoids in the prevention of cardiometabolic diseases in adults [8]. Nevertheless, to date, few studies about (poly)phenols and cardiometabolic health have been carried out in adolescents, generating the question of whether dietary (poly)phenols could have an effect on cardiometabolic health in this target population [9][10][11][12][13][14][15]. In the HELENA study, Wisnuwardani et al estimated dietary (poly)phenol intake in European adolescents through 2 non-consecutive 24h dietary recalls, and they found associations between total (poly)phenol intake (TPI) and body mass index (BMI) in a cross-sectional analysis and between lignan intake and a lower metabolic syndrome risk over time [9,10,16].…”
Section: Introductionmentioning
confidence: 99%